Analysis of cis-regulatory elements in the 5' flanking region of the Drosophila melanogaster choline acetyltransferase gene - Kitamoto, T (J Neurosci, 1992)
We have analyzed the cis-regulatory elements in the 5′ flanking region of the Drosophila choline acetyltransferase gene (ChAT, E.C.2.3.1.6). DNA fragments were fused to the Escherichia coli lacZ reporter gene and introduced into the Drosophila germ line by P-element-mediated transformation. A 7.4 kb 5′ flanking sequence directed beta- galactosidase expression in the adult optic lobes and other well- defined CNS structures with a pattern very similar to the distribution of endogenous ChAT protein. In contrast, the proximal 3.3 kb and 1.2 kb of 5′ flanking DNA directed lacZ expression in only selected subsets of the structures seen with the 7.4 kb lacZ construct. Our results indicate that both qualitative and quantitative regulatory elements are present in the 5′ flanking DNA and that these elements distinguish various subsets of cholinergic neurons. We have also fused the same 5′ flanking DNA sequences to wild-type ChAT cDNA and used these constructs to transform Chatsl mutant flies. Not only the 7.4 kb cDNA construct, but also the 3.3 and 1.2 kb constructs, rescued Chatsl from temperature- dependent paralysis and adult lethality, indicating that the regulatory information in any of these genomic fragments can drive sufficient wild- type ChAT expression to overcome these mutant phenotypes.